2012
DOI: 10.1108/17506121211259403
|View full text |Cite
|
Sign up to set email alerts
|

Brand salience of OTC pharmaceuticals through package appearance

Abstract: Purpose -The changing health care market is affecting consumers who are now expected to take greater responsibility for their health. Their means for doing this include purchasing self-medication and medical self-service, which coincides neatly with an increase in the number of over-the-counter (OTC) pharmaceuticals. Additionally, OTC pharmaceuticals are progressively becoming available in a wider range of stores, where the pharmacists' knowledge of the OTC products is absent. This study aims to examine packag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 79 publications
(139 reference statements)
1
45
0
Order By: Relevance
“…Kauppinen et al . (2012) suggest that instead of viewing packaging as an external cue of the product, it could be seen as an integral part of the brand and as an in‐store media conveying the brand identity and message at the point of purchase. Thus, it is important to understand the effect and functions of the various verbal/numerical (brand name, manufacturer, country of origin and price) and visual extrinsic product cues (size, shape, material, graphics, picture, letter font and colour) that contribute to the holistic brand packaging experience …”
Section: Packaging Design Is a Strategic Brand Issuementioning
confidence: 99%
See 4 more Smart Citations
“…Kauppinen et al . (2012) suggest that instead of viewing packaging as an external cue of the product, it could be seen as an integral part of the brand and as an in‐store media conveying the brand identity and message at the point of purchase. Thus, it is important to understand the effect and functions of the various verbal/numerical (brand name, manufacturer, country of origin and price) and visual extrinsic product cues (size, shape, material, graphics, picture, letter font and colour) that contribute to the holistic brand packaging experience …”
Section: Packaging Design Is a Strategic Brand Issuementioning
confidence: 99%
“…Interestingly, though, it has been shown that high‐risk products such as pharmaceuticals may unconsciously be chosen for their packaging colours. For these products, the impact of packaging colour varies according to product type, age of purchaser and nationality. This is explained by the varying meanings that colour communicates, suggesting that visual extrinsic cues are in fact used as informative cues, even for high‐involvement products in situations characterized by haste, a low level of product knowledge and possibly also health illiteracy.…”
Section: When Does Packaging Colour Have An Impact?mentioning
confidence: 99%
See 3 more Smart Citations